A dormant TIL phenotype defines non-small cell lung carcinomas sensitive to immune checkpoint blockers - S. N. Gettinger (Nature Portfolio, 2018)
Immune checkpoint blockade (ICB) only induces tumour response in a subset of non-small cell lung carcinomas (NSCLC). Here the authors do whole genome sequencing and multiplexed quantitative immunofluorescence on patient samples and identify a “dormant” T-cell signature associated with sensitivity to ICB.